Using Environmental Modification and Teacher Mediation to Increase Literacy Behaviors in Inclusive Preschool Settings. Issue 4 (October 2020) - Deris, Aaron R.; DiCarlo, Cynthia F.; Wagner, Dana; Krick Oborn, Kellie
Abstract : It is considered a recommended practice to integrate literacy concepts into child-initiated choice center time long before formal reading instruction begins. The purpose of this study was to determine whether environmental modification and a teacher-mediated literacy intervention would increase child engagement of literacy behaviors during free choice time in the classroom. Data were collected on the literacy behaviors of 9 children across 3 inclusive preschool classrooms in a suburban public school system. A multiple baseline design was used to determine the effects of an environmental modification using the Early Language and Literacy Classroom Observation and a teacher-mediated intervention on children's literacy behaviors. Results included an average increase of 43 percentage points (range = 39–45 percentage points) in observed literacy behaviors in each of the 3 classrooms. Individual children in each classroom demonstrated an increase in literacy behaviors from baseline to intervention. These results are consistent with previous research, which indicated that the modification of the environment and teacher mediation increase literacy behaviors.